Ureia protegida ou comum em substituição ao farelo de soja nas características pós abate de novilhos confinados - Cardoso, Gilmar dos Santos (2016)
This study aimed to evaluate the effect of using the protected or common urea in place of the true protein obtained from the soybean meal on body tissues not belonging the carcass, as well as analyzing the qualitative and quantitative characteristics of the carcass and meat of feedlot finished steers. It was used 27 castrated male steers, pure and crossbred (Charolais x Nellore), age and average weight of 20 months and 293 kg respectively, distributed in three treatments: Protected Urea - concentrate containing slow degradation urea; Soybean Meal - concentrate containing soybean meal; Common Urea - concentrate containing agricultural urea. The diet was calculated to meet the nutritional minimum requirements to obtain an average daily gain in weight of 1.5 kg / animal, estimating a dry matter intake of 2.65 kg / 100 kg body weight. The experimental design was randomized blocks (racial predominance), with three treatments and nine replications, being the animal the experimental unit. Diets did not provide significant differences in the empty body weight (EBW) due to the similarity in slaughter weights (SW). Similarity between the treatments was also observed in EBW / SW relationship, with average values of 0.87 for the treatments containing non-protein nitrogen and 0.88 for soybean meal treatment. The gastrointestinal content in absolute weight and in relation to the empty body weight showed similarity in the diets tested, with average values of 54.33 kg and 13.52%, respectively. The diets of the treatments did not influence the blood volume of animals, following the similarity in the internal organs. Steers receiving protected urea showed higher omaso weight on 100 kg of EBW (P <0.05) compared to animals fed with soybean meal, with superiority of 32.38%. Dietary treatments did not affect the weights and hot and cold carcass yields. The thickness of fat overlying the substrate was not changed in accordance with the diets studied, the average fat thickness was 3.97 mm. The measures and carcass compactness were unaffected by the diets, with mean values of 127.55; 74.86; 39.86; 38.84 and 25.72 cm for carcass length, leg and arm, arm perimeter and cushion thickness, respectively. A significant difference in marbling was observed, soybean meal treatment was superior to treatment with protected urea (3.72 vs. 2.28 points) and were classified as "traits." Thus, it was observed that the use of protected or common urea showed similar behavior in the ratings after slaughter of the animals, both in the non-carcass components and the carcass and meat characteristics. Due to the results of this study, there is need for increased research in the use of alternative food in the termination of bovines, to bring improvements in production at the lowest cost. Such importance must be understood by the fact that the termination be the most costly phase in the life of animals.